Genetic Association of Finger Photoplethysmography-Derived Arterial Stiffness Index with Blood Pressure and Coronary Artery Disease - Zekavat, Seyedeh M. (Arterioscler Thromb Vasc Biol, 2019)
OBJECTIVE: Arterial stiffness index (ASI) is independently associated with blood pressure and coronary artery disease (CAD) epidemiologically. However, it is unknown whether these associations represent causal relationships. Here, we assess whether genetic predisposition to increased ASI is associated with elevated blood pressure and CAD risk. APPROACH AND RESULTS: We first performed a large-scale epidemiologic association of finger photoplethysmography-derived ASI in the UK Biobank, finding significant associations with systolic blood pressure (SBP; Beta 0.55mmHg, [95% CI, 0.45–0.65], P=5.77×10(−24), N=137,858), diastolic blood pressure (DBP; Beta 1.05mmHg, [95% CI, 0.99–1.11], P=7.27×10(−272), N=137,862), and incident CAD (HR 1.08 [95% CI, 1.04–1.11], P=1.5×10(−6); N=3,692 cases, 126,615 controls) in multivariable models. We then performed an ASI genome-wide association analysis (GWAS) in 131,686 participants from the UK Biobank. Across participants not in the ASI GWAS, a 6-variant ASI polygenic risk score was calculated. Each SD increase in genetic ASI was associated with SBP (Beta 4.63mmHg [95% CI, 2.1–7.2]; P=3.37×10(−4); N=208,897), and DBP (Beta 2.61mmHg [95% CI, 1.2–4.0]; P=2.85×10(−4); N=208,897); however, no association was observed with incident CAD (HR 1.12 [95% CI, 0.55–2.3]; P=0.75; N=223,061; 7,534 cases). The lack of CAD association observed was replicated among 184,305 participants (60,810 cases) from the Coronary Artery Disease Genetics Consortium (OR 0.56 [95% CI, 0.26–1.24]; P=0.15). CONCLUSIONS: Our data support the conclusion that finger photoplethysmography-derived ASI is an independent, genetically causal risk factor for blood pressure, but do not support the notion that ASI is a suitable surrogate for CAD risk.